The efficacy of the heat killing of Mycobacterium tuberculosis. Issue 10 (1st October 2002) - Doig, C; Seagar, A L; Watt, B; Forbes, K J
Abstract : There is concern that current procedures for the heat inactivation of Mycobacterium tuberculosis may not be adequate. This raises serious safety issues for laboratory staff performing molecular investigations such as IS6110 restriction fragment length polymorphism typing. This paper confirms that the protocol of van Embden et al, as performed routinely in this laboratory, is safe and effective for the heat inactivation of M tuberculosis . This procedure involves complete immersion of a tube containing a suspension of one loopfull of growth in a water bath at 80°C for 20 minutes. Seventy four isolates were included in this investigation. Despite prolonged incubation for 20 weeks, none of the heat killed M tuberculosis suspensions produced visible colonies or gave a positive growth signal from liquid culture. This method did not affect the integrity of the DNA for subsequent molecular investigations.